The Role of Economic Growth and Economic Freedom in Moderating the Influence of Bank Health Performance on Profitability - Sabrina, Siti Nabila Zida; Miranti, Titis (Islamic Economics Journal, 2025)
This study aims to analyze the effect of bank soundness on the profitability of Islamic Banks in Indonesia, with economic growth and economic freedom as moderating variables. Bank soundness is measured using the RGEC approach. This study adopts a quantitative approach, employing panel data regression analysis and Moderated Regression Analysis (MRA). The data used consist of annual secondary data from 2011 to 2024, including financial ratios from the annual reports of Islamic commercial banks in Indonesia, as well as data on Indonesia’s economic growth and economic freedom. The results show that bank soundness has a significant effect on profitability, except for GCG. Economic growth and economic freedom moderate the relationship between all independent variables and the dependent variable, except for GCG. These findings emphasize the importance of strengthening internal bank factors and macroeconomic support to enhance the profitability of Islamic banking in Indonesia.